2020
DOI: 10.24093/awej/vol11no4.1
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behavior and Emotional Intelligence of EFL Teachers in Saudi Arabia: Implications to Teaching Performance and Institutional Effectiveness

Abstract: Many studies have extensively investigated the antecedents, consequences, and relationships of Organizational Citizenship Behavior (OCB) and Emotional Intelligence (EI) in corporate and industrial settings, but not in educational contexts particularly in the field of English language teaching. To expand the existing literature in OCB and EI, this study investigated the levels and relationship of OCB and EI of college English teachers in an English language institute in the western region of Saudi Arabia. It tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It increases job happiness, mental health, physical health, job retention, and service-oriented behaviours among employees by facilitating information exchange [40]. Displaying OCBs can also increase organisational efficiency by reducing the need for monitoring, training, and crisis management expenditures, allowing managers to focus on more critical job duties, and encouraging workers to contribute constructive comments that can help the businesses to develop [41]. OCBs are vital in generating improved levels of organisational productivity, quality, and effectiveness in general [42].…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
“…It increases job happiness, mental health, physical health, job retention, and service-oriented behaviours among employees by facilitating information exchange [40]. Displaying OCBs can also increase organisational efficiency by reducing the need for monitoring, training, and crisis management expenditures, allowing managers to focus on more critical job duties, and encouraging workers to contribute constructive comments that can help the businesses to develop [41]. OCBs are vital in generating improved levels of organisational productivity, quality, and effectiveness in general [42].…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
“…Altruism involves behaviours of helping co-workers (Meniado, 2020). These help an organization promote efficiency through reduced need for supervision, training, and crisis management costs (Pickford & Joy, 2016).…”
Section: Career Development and Altruismmentioning
confidence: 99%
“…Furthermore, the employee within an excellent OC would develop willingness for good behaviour to complete activities outside the main occupation (Widayati & Gunarto, 2017). In order to widen a tradition of willingness and commitment in an educational institution, it is essential to identify and promote the characteristics and actions that lead to OCB (Meniado, 2020). Hence, to fight the scourge of incessant turnover and poor performance, the principles of OC could be deployed.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have indicated that self-awareness as a part of EI relates to OCB ( Rizki et al 2019 ) and that the regulation of emotion as an indicator of EI affects OCB ( Gan and Yusof 2018 ; Perveen et al 2021 ). Furthermore, EI influences civic virtue, altruism, and conscientiousness as OCB indicators ( Majeed et al 2017 ; Meniado 2020 ; Mariyanti et al 2021 ). This indicates that EI is an essential predictor of OCB.…”
Section: Introductionmentioning
confidence: 99%